Manajemen Masjid Baitul Mustahfirin Al-Amir dalam Kegiatan Keagamaan - Guruh Sakti Syahputra; Hasnun Jauhari Ritonga (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research is related to the Management of the Baitul Mustaghfirin Al-Amir Mosque in religious activities. The purpose of this study was to determine the management of the mosque in religious activities and to find out the supporting and inhibiting factors in religious activities at the Baitul Mustaghfirin Al-Amir Mosque, Jalan Mahoni Psr II Timur, Bandar klippa Village, Kec. Percut Sei Tuan Kab. Deli Serdang. This type of research is a qualitative research with a descriptive qualitative approach. Data obtained by using observation, interviews and documentation. Based on research that the Baitul Mustaghfirin Al-Amir Mosque in religious activities carries out management functions, namely planning and organizing activities, compiling and allocating schedules, assigning tasks, carrying out planned activities, these management functions are naturally carried out to facilitate religious activities. Carrying out activities or activities The mosque functions as a place for various religious activities and not just a place of ritual worship. In carrying out activities, there are several factors that become obstacles to activities, including: 1) Lack of awareness to routinely monitor or participate in activities. 2) There are those who work until late at night, so they rarely participate in these activities. Keywords: Management, Mosque, Religious Activities